THE INFLUENCE OF EL NIÑO ON RAINFALL VARIABILITY IN NORTH SUMATRA PROVINCE - Hendri Irwandi; Mulkan Iskandar; Edison Kurniawan; Yeni Megalina (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2017)
El Niño is a global phenomenon that affects the variability of rainfall in the Province of North Sumatra, Indonesia. The impact of El Niño will be different for each region. This review will analyse the influence of El Niño activity on seasonal and annual rainfall variability. In this research, North Sumatra Province will be divided into 4 (four) regions based on its topographical conditions, such as: East Coast (EC), East Slope (ES), Mountains (MT), and West Coast (WC). The method used was statistical and descriptive analysis. Data used in this research were rainfall data from 15 stations/climate observation posts which is spread in North Sumatera region and anomaly data of Nino 3.4 region over the period 1981 – 2016. The results showed that the active El Niño had an effect on the decreasing of rainfall in the period of DJF, JJA, and SON in East Coast, East Slope, and Mountains with an average annual percentage decline up to 7%.Keywords: El Niño, rainfall, variability, and North Sumatra.